Pleistocene dynamics of the Eurasian steppe as a driving force of evolution: Phylogenetic history of the genus Capsella (Brassicaceae). Issue 18 (18th August 2021) - Žerdoner Čalasan, Anže; Hurka, Herbert; German, Dmitry A.; Pfanzelt, Simon; Blattner, Frank R.; Seidl, Anna; Neuffer, Barbara
Abstract: Capsella is a model plant genus of the Brassicaceae closely related to Arabidopsis . To disentangle its biogeographical history and intrageneric phylogenetic relationships, 282 individuals of all five currently recognized Capsella species were genotyped using a restriction digest‐based next‐generation sequencing method. Our analysis retrieved two main lineages within Capsella that split c . one million years ago, with western C. grandiflora and C. rubella forming a sister lineage to the eastern lineage consisting of C. orientalis . The split was attributed to continuous latitudinal displacements of the Eurasian steppe belt to the south during Early Pleistocene glacial cycles. During the interglacial cycles of the Late Pleistocene, hybridization of the two lineages took place in the southwestern East European Plain, leading to the allotetraploid C. bursa‐pastoris . Extant genetic variation within C. orientalis postdated any extensive glacial events. Ecological niche modeling showed that suitable habitat for C. orientalis existed during the Last Glacial Maximum around the north coast of the Black Sea and in southern Kazakhstan. Such a scenario is also supported by population genomic data that uncovered the highest genetic diversity in the south Kazakhstan cluster, suggesting that C. orientalis originated in continental Asia and migrated north‐ and possibly eastwards after the last ice age. Post‐glacial hybridization events between C. bursa‐pastoris and C. grandiflora/rubella in the southwestern East European Plain and the Mediterranean gave rise to C. thracica . Introgression of C. grandiflora / rubella into C. bursa‐pastoris resulted in a new Mediterranean cluster within the already existing Eurasian C. bursa‐pastoris cluster. This study shows that the continuous displacement and disruption of the Eurasian steppe belt during the Pleistocene was the driving force in the evolution of Capsella . Abstract : Capsella is a model plant genus of the Brassicaceae, closely related to Arabidopsis . We present here the evolutionary history of the genus Capsella placed into space and time.